Identification of potential biomarkers of oral squamous cell carcinoma using integrated proteomics and glycoproteomics and glycoproteomics analyses / Wong Yin Ling - Wong, Yin Ling (2020)
Oral cancer is one of the major health concerns worldwide. The 5-year survival rate of oral squamous cell carcinoma (OSCC) has remained at approximately 50% over the past decades. Most OSCCs are diagnosed at an advanced stage due to the delay in diagnosis, suggesting an imperative need in identifying reliable biomarkers to improve the diagnosis, prognosis, and treatment of OSCC. This study aimed to identify potential biomarkers that are involved in the development and progression of OSCC using integrated proteomics and glycoproteomics analyses. Proteomics analysis was performed on serum samples of 10 patients with oral potentially malignant disorder (OPMD), 40 patients with OSCC, and 10 healthy volunteers as control using two-dimensional gel electrophoresis (2-DE) followed by silver staining. Based on the analysis, 5 proteins (AAT, APOA1, IGKC, SAMP, and VDBP) were up-regulated and 5 (AMBP, CLU, HP, PRDX2, and RBP4) down-regulated in OPMD when compared with control (p < 0.05). In OSCC, 4 proteins (IGHA2, IGHG2, IGKC, and TF) were up-regulated and 5 (ALB, AMBP, CLU, HP, and LRG1) down-regulated in the early stage of OSCC, whereas 5 proteins (AAT, APOA1, C3, IGHG2, and VDBP) were up-regulated and one (PRDX2) down-regulated in the advanced stage of OSCC when compared with control (p < 0.05). As for glycoproteomics analysis, the serum samples were subjected to 2-DE coupled with Concanavalin A and Jacalin lectin for the detection of N- and O-glycosylated proteins, respectively. A total of 5 glycoproteins (AAT, AHSG, APOA1, CLU, and HP) that exhibited tumour-specific glycosylation changes in OPMD and OSCC were identified. Most of these identified proteins and glycoproteins were acute-phase proteins, which indicated the presence of chronic inflammation in OSCC. Furthermore, bioinformatics iv analysis revealed the involvement of the identified proteins in platelet degranulation, activation of classical complement pathway, LXR/RXR activation, and acute phase response signalling pathways during development and progression of OSCC. Based on these findings, AAT, AHSG, APOA1, CLU, and HP were selected for further validation using enzyme-linked immunosorbent assay (ELISA) and immunohistochemistry (IHC). In the ELISA analysis, AAT, AHSG, APOA1, CLU, and HP showed consistent findings with the proteomics and glycoproteomics analyses. However, based on the IHC results, only CLU and HP were found to be corroborated with the findings. These identified potential biomarkers may play important roles to improve the detection of OSCC. Nevertheless, further investigation is warranted to determine their roles in OSCC. Keywords: Oral Squamous Cell Carcinoma, Biomarker, Proteomics, Glycoproteomics, Lectin